2018
DOI: 10.1186/s12888-018-1648-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors associated with the mental health of young adults in Kabul, Afghanistan

Abstract: BackgroundWe examined the mental health status and severity of psychological distress symptoms among young adults residing in Kabul, Afghanistan and determined how such outcomes might be influenced by an array of risk and protective factors.MethodsA cross-sectional study design was adopted using convenience, snowball, and street-intercept recruitment techniques. Surveys were completed by 232 young adults between 18 and 35 years of age in September 2015. We used both etic (mental health component of the SF-8) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
2
30
3
Order By: Relevance
“…However, there is very limited research exploring the relationship between hope and depression during the ongoing COVID-19 pandemic. Hope has also been well established as a factor associated with the process of resilience following exposure to adversities [49][50][51][52]. Notably, prior research showed that hope can be increased through different therapeutic approaches or interventions [53][54][55].…”
Section: The Mediating Role Of Resilience and Hopementioning
confidence: 99%
“…However, there is very limited research exploring the relationship between hope and depression during the ongoing COVID-19 pandemic. Hope has also been well established as a factor associated with the process of resilience following exposure to adversities [49][50][51][52]. Notably, prior research showed that hope can be increased through different therapeutic approaches or interventions [53][54][55].…”
Section: The Mediating Role Of Resilience and Hopementioning
confidence: 99%
“…Afghanistan is a conflict-affected country that has been at war for over four decades. Exposure to trauma among women and families is high and mental health issues are widespread [43,44]. Women face additional challenges in a largely patriarchal society, with restrictions on their movement, access to financial resources and high levels of domestic violence [43].…”
Section: Discussionmentioning
confidence: 99%
“…The consent process, recruitment and survey administration procedure along with details on the use of specific scales are described in full detail elsewhere (Alemi et al, ). In order to measure participants' intent to stay in Afghanistan, we used a single item measure asking participants ‘Do you plan on leaving Afghanistan to seek refuge elsewhere in the near future?’ with a binary ‘yes–no’ response choice.…”
Section: Methodsmentioning
confidence: 99%